2011
DOI: 10.1073/pnas.1018027108
|View full text |Cite
|
Sign up to set email alerts
|

Microbial growth at hyperaccelerations up to 403,627 × g

Abstract: It is well known that prokaryotic life can withstand extremes of temperature, pH, pressure, and radiation. Little is known about the proliferation of prokaryotic life under conditions of hyperacceleration attributable to extreme gravity, however. We found that living organisms can be surprisingly proliferative during hyperacceleration. In tests reported here, a variety of microorganisms, including Gram-negative Escherichia coli, Paracoccus denitrificans, and Shewanella amazonensis; Gram-positive Lactobacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…Although their total metabolic energy is hundred of thousands times smaller than their gravitational energy, they are appeared and lived for a billions years ago under the influence of the Earth gravitation without significant changes in their cellular characteristics. Actually, in the scientific literature predominates the concept, that the Unicellular organisms are not presumed to be gravity sensing [21,22,23]. The experiments on growth of Unicellular on hypergravity and microgravity conditions confirm this concept.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Although their total metabolic energy is hundred of thousands times smaller than their gravitational energy, they are appeared and lived for a billions years ago under the influence of the Earth gravitation without significant changes in their cellular characteristics. Actually, in the scientific literature predominates the concept, that the Unicellular organisms are not presumed to be gravity sensing [21,22,23]. The experiments on growth of Unicellular on hypergravity and microgravity conditions confirm this concept.…”
Section: Resultssupporting
confidence: 61%
“…The experiments on growth of Unicellular on hypergravity and microgravity conditions confirm this concept. The study of Deguchi et al [23] showed that microbial growth is possible up to hyperaccelerations ~10 5 ×g (g=9.8 m/s 2 ). The small hyperacceleration to about ~10×g can not affect growth of Gram-negative prokaryotes (E. coli, Paracoccus denitrificans, Shewanella amazonensis) and Gram-positive prokaryotes (Lactobacillus delbrueckii).…”
Section: Resultsmentioning
confidence: 99%
“…Escherichia coli and another Gram‐negative bacterium Paracoccus denitrificans can proliferate even at 403,627 times the force of gravity. The Gram‐positive bacterium Lactobacillus delbrueckii (used to make yoghurt) and the unicellular fungus Saccharomyces cerevisiae (Baker's yeast) proliferated at 22,505 times the force of gravity . Hypergravity reduced proliferation.…”
Section: Killer Bugs From Spacementioning
confidence: 99%
“…The bacteria were cultured after being rotated in an ultracentrifuge at a high speed: 403,627 × g. Analysis showed that the small size of prokaryotic cells is essential for successful growth under hypergravity. This research implicates the feasibility of panspermia (Deguchi et al, 2011). …”
Section: Escherichia Coli: a Candidate Extremophilementioning
confidence: 99%